Measuring the Effectiveness of Multimedia Use in Micro-Credential Game Developer Programs through Simple Additive Weighting (SAW) - yanto, Muji (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2024)
This study aims to assess the effectiveness of multimedia use in the Micro-Credential Game Developer Program using the Simple Additive Weighting (SAW) method. Given the significant growth of the game industry in Indonesia, enhancing the quality of local games through human resource development via micro-credential programs is a primary focus. This quantitative research collected data from 101 lecturers and 22 students using a Likert Scale-based questionnaire to evaluate various learning media. The SAW calculation results indicate that Video and Audio media are rated as the most effective, achieving the highest scores of 1 (82.57% for Video and Audio) based on criteria such as ease of understanding, improvement in learning effectiveness, and motivation. Conversely, Teks media received the lowest score of 0.8 (64%), indicating challenges in material comprehension. The study's conclusions affirm the importance of audiovisual media in enhancing the quality of game development learning and provide recommendations for integrating these media into the game education curriculum. Despite offering valuable insights, the study acknowledges limitations related to the limited sample scope, suggesting a need for further research for broader exploration and validation of findings.